2016
DOI: 10.1016/j.ijsu.2016.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Transtibial vs anatomical single bundle technique for anterior cruciate ligament reconstruction: A Retrospective Cohort Study

Abstract: Single-bundle anatomic ACL reconstruction was better than the TT in term of clinical, functional, and laboratory results. We believe that AT ACL reconstruction will increase in use and traditional method which is TT ACL reconstruction surgery will decrease in the long term. Theoretically, anatomic relocation of the ACL can provide better knee kinematics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Although, there is no need to worry about the iatrogenic problems that are potential complica-tions in the transportal technique, it is relatively demanding to reach the center of the native ACL footprint using this technique. 35,37,72,78,79,82,87 In the outside-in technique, no restrictions exist for femoral tunnel placement. However, special devices such as a backward drill are required, and a femoral incision is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, there is no need to worry about the iatrogenic problems that are potential complica-tions in the transportal technique, it is relatively demanding to reach the center of the native ACL footprint using this technique. 35,37,72,78,79,82,87 In the outside-in technique, no restrictions exist for femoral tunnel placement. However, special devices such as a backward drill are required, and a femoral incision is needed.…”
Section: Discussionmentioning
confidence: 99%
“…have reported that the traditional transtibial technique is unsuitable, and the superiority of the transportal technique has been suggested. [33][34][35][36][37][38] In the transportal technique, the femoral tunnel is created from the medial or far-medial portal. Using this technique, surgeons are able to drill deep and low tunnels in the femoral intercondylar notch.…”
mentioning
confidence: 99%
“…It is shown that anatomical approach brought the tunnel layout to a more horizontal position and thus biomechanical studies have shown that in the coronal plane, it provides the anterior-posterior and the internal rotational stability better ( Kilinc et al, 2016 ; Miller et al, 2011 ; Scopp et al, 2004 ; Seon et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, 36 hamstring tendons were obtained from the same limbs for ACL reconstruction. The hamstring grafts were prepared as the traditional single-bundle technique [28] . Two ends of the graft were woven separately for about 3.5 cm with a diameter of 8 mm and a length of 8.5 cm, and the grafts were left to defrost in isotonic saline (0.9% NaCl solution) for 1 hour prior to the test ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The tunnel was prepared according to the traditional single-bundle technique in Groups B, C, and D, following a published protocol [28] . Using a 55° tibial drill guide, a trained surgeon advanced a guide wire into the centre of the tibial footprint, and an 8-mm tibial tunnel was drilled over the guide wire.…”
Section: Methodsmentioning
confidence: 99%